Automated Controlled Stirred Liquid Baths System for Calibrating Contact Thermometers in the Temperature Range from -80°C to 420°C - mohamed, Doaa; El-Matarawy, Ahmed; Mohy, Eman (Journal of Advanced Research Design, 2024)
National Institute of Standards (NIS) is the national metrology institute in Egypt. It consists of more than twenty laboratories working continuously to realize the international standard units (SI units). Thermal metrology laboratory (ThML) is one NIS leading laboratory that has twice responsibilities, one for realizing the thermodynamic temperature and the other for introducing calibration solutions to all organizations in Egypt such as contact, non-contact thermometry, hygrometry, thermal analysis and viscosity. In this study, a newly developed automated firmware was used for controlling and regulating the temperature of stirred liquid baths and thermometry bridge system (SLBTBS) simultaneously and determined precisely the starting time of the measurements according to smart algorisms using compatible parameters of (LabVIEW®) tools. The protocol of measurements was dependent on an automatic investigation of the best stability period whereby the setting point lied in the specific temperature ranges related to hysteresis limits. Characterization tests and assessment for optimum conditions of the SLBTBS were done. The newly designed controller gave temperature stability better than 0.02K in the low-temperature range with better-linked uncertainty.